Incidence and Outcomes of Acute Respiratory Distress Syndrome: A Nationwide Registry-Based Study in Taiwan, 1997 to 2011. Issue 43 (October 2015) - Chen, Wei; Chen, Yih-Yuan; Tsai, Ching-Fang; Chen, Solomon Chih-Cheng; Lin, Ming-Shian; Ware, Lorraine B.; Chen, Chuan-Mu
Abstract : Abstract: Most epidemiological studies of acute respiratory distress syndrome (ARDS) have been conducted in western countries, and studies in Asia are limited. The aim of our study was to evaluate the incidence, in-hospital mortality, and 1-year mortality of ARDS in Taiwan. We conducted a nationwide inpatient cohort study based on the Taiwan National Health Insurance Research Database between 1997 and 2011. A total of 40, 876 ARDS patients (68% male; mean age 66 years) were identified by International Classification of Diseases, 9th edition coding and further analyzed for clinical characteristics, medical costs, and mortality. The overall crude incidence of ARDS was 15.74 per 100, 000 person-years, and increased from 2.53 to 19.26 per 100, 000 person-years during the study period. The age-adjusted incidence of ARDS was 15.19 per 100, 000 person-years. The overall in-hospital mortality was 57.8%. In-hospital mortality decreased from 59.7% in 1997 to 47.5% in 2011 ( P  < 0.001). The in-hospital mortality rate was lowest (33.5%) in the youngest patients (age 18–29 years) and highest (68.2%) in the oldest patients (>80 years, P  < 0.001). The overall 1-year mortality rate was 72.1%, and decreased from 75.8% to 54.7% during the study period. Patients who died during hospitalization were older (69 ± 17 versus 62 ± 19, P  < 0.001) and predominantly male (69.8% versus 65.3%, P  < 0.001). In addition, patients who died during hospitalization had significantly higher medical costs (6421 versus 5825 US Dollars, P  < 0.001) and shorter lengths of stay (13 versus 19 days, P  < 0.001) than patients who survived. We provide the first large-scale epidemiological analysis of ARDS incidence and outcomes in Asia. Although the overall incidence was lower than has been reported in a prospective US study, this may reflect underdiagnosis by International Classification of Diseases, 9th edition code and identification of only patients with more severe ARDS in this analysis. Overall, there has been a decreasing trend in in-hospital and 1-year mortality rates in recent years, likely because of the implementation of lung-protective ventilation.